lg4+lg9+2*根号下(lg6)^2-2lg6+1=?
1个回答
lg4+lg9+2*根号下(lg6)^2-2lg6+1
=LG4+LG9+2根号(LG6-1)方
=LG36+2(1-LG6)
=6LG6-2LG6+2
=4LG6+2
相关问题
已知lg2=0.3010,lg3=0.4771,计算:(1)lg9/2;(2)lg3.6;(3)lg根号6/2
对数化简化简√lg6lg6-4lg2lg3√(lg6lg6-4lg2lg3)
lg2=0.3010,lg3=0.4771,求lg(3/2),lg 2.4 lg根号6
lg5·lg8000+(lg2^根号3)^2-lg6+lg0.06
【根号lg9-lg9+lg10×(lg根号27+lg8-lg根号1000)】÷(lg0.3)(lg1.2)
lg2+lg3+根号(lg6)^2+log以6为底6-2lg6 求值
计算1+Lg0.001+(根号下Lg²1/3-4Lg3+4)+Lg6-Lg0.02
【根号(lg3的平方-lg9+1)*(lg根号27+lg8-lg根号1000)】/(lg0.3)*(lg1.2)
lg5 (lg8+lg1000)+(lg2 )(lg2 )+lg0.06+lg1/6
计算:(25/9)^0.5+(64/27)^1/3+lg6+根号(lg6)^2-lg36+1